Can a disaster affect rheumatoid arthritis status? A retrospective cohort study after the 2011 triple disaster in Fukushima, Japan. (26th April 2018) - Ochi, Sae; Kato, Shigeaki; Leppold, Claire; Morita, Tomohiro; Tsubokura, Masaharu; Oikawa, Tomoyoshi; Shineha, Ryuzaburo; Kanazawa, Yukio; Fujiwara, Masatoshi
Abstract: Objective: As status of rheumatoid arthritis (RA) is highly affected by environmental factors, a catastrophic disaster may also affect RA activity. Herein we conducted a retrospective cohort study in the disaster area of the 2011 triple disaster in Fukushima, Japan: an earthquake, tsunamis and a nuclear accident. Methods: Clinical records of RA patients who attended a hospital near the Fukushima Daiichi Nuclear Power Plant were collected. For those who underwent whole‐body counter testing, internal radiation exposure levels were also collected. As clinical parameters may fluctuate in the absence of a disaster, changes in values before and after the disaster were also compared. Logistic regression was conducted to identify factors affecting RA status. Results: Fifty‐three patients (average age, 64.2 years; females, 83%; average disease duration, 15.7 years) were included in the study. Five patients lived within the no‐entry zone, 37 evacuated immediately after the disaster, and four temporarily stopped RA treatment. The proportions of patients who showed worsened tender joint counts, swollen joint counts and rheumatoid factor values were significantly higher after the disaster compared to those before. Among the 16 patients who underwent whole‐body counter testing, only one showed a detectable, but negligible, radioactive cesium level. Use of methotrexate was identified as a possible preventive factor for RA exacerbation in this setting. Conclusion: This is the first study to analyze detailed profiles of RA patients after a disaster. As methotrexate may prevent disease exacerbation, continuity of care for this common chronic disease should be considered in disaster settings.